Synthesis, Compositional, Morphological, Structural, and Thermal Properties of Eggshell Calcium Oxide for Solar Photovoltaic Glass (Lafia Journal of Scientific and Industrial Research, 2025)
The increasing demand for sustainable materials in engineering applications has prompted the exploration of eco-friendly alternatives. Conventional calcium oxide (CaO) production from limestone is energy-intensive and environmentally detrimental, prompting interest in biogenic alternatives such as poultry eggshell waste, predominantly composed of calcium carbonate. Despite extensive research into eggshell-derived CaO for catalytic and biomedical applications, its potential for photovoltaic glass applications, particularly considering region-specific variations in material properties, has not been adequately investigated. This study comprehensively evaluates CaO extracted from chicken eggshells sourced from Lafia Local Government Area, Nasarawa State, Nigeria, to establish its suitability for photovoltaic glass manufacturing. The extraction process involved thermal calcination at 900 °C for two hours, followed by detailed compositional, morphological, structural, and thermal characterizations using XRF, SEM-EDS, XRD, and TGA techniques. The results demonstrated brilliant white powder with high compositional purity (98.58% CaO), nanoscale spherical morphology conducive to uniform integration in glass matrices, robust crystallinity beneficial for structural stability, and strong thermal resilience crucial for high-temperature processing. These findings highlight eggshell-derived CaO as an economically viable, sustainable, and high-performance alternative for PV glass manufacturing. Further studies are recommended to assess practical integration in PV glass formulations, long-term durability, study of farming systems, and lifecycle economic viability.
Keywords: sustainability; biogenic material; circular economy; eggshell calcium oxide; calcination; eco-friendly; photovoltaic